Mother's Decision for Postpartum Care at Home in Kupang Regency, East Nusa Tenggara Province: Cultural Analysis that Influences the Choice of Postpartum Care at Home - Abuk Seran, Agustina; Matje Meriaty Huru; Nurlaelah Al-Tadom; Maria Florentina Nining Kosad (SABDA EDU PRESS (SEP), 2024)
Postpartum care at home is still common in some, including in Kupang Regency, East Nusa Tenggara (NTT) Province. many mothers in Kupang, postpartum care at home is not only practical but also part of a tradition that has been passed down from generation to generation. However, this choice can increase health risks without adequate medical support. Therefore, it is important to understand how local culture influences this decision so that solutions to improve maternal and infant health can be found. This study examines the influence of local culture and traditions on mothers' decisions to choose postpartum care at home. Using a qualitative approach and ethnographic design, this study describes postpartum care practices in Kupang Regency. In-depth interviews were conducted with mothers undergoing postpartum care, traditional birth attendants, and health workers. Data were collected from August to October 2023 and analyzed using six steps of qualitative methods. The study's results identified three local cultural themes that influence postpartum care at home: 1) Postpartum taboos, as well as postpartum care traditions; 2) Family support; and 3) Belief in traditional birth attendants. This practice hinders mothers from utilizing available health facilities. This study recommends cultural integration in health education programs, increased collaboration between medical personnel and traditional birth attendants, and policies that support culturally friendly health access.